EDITORIAL: The IJIEM as a platform for engagement - Marjanovic, Ugljesa (International Journal of Industrial Engineering and Management, 2020)
IJIEM was founded in 2010 by professor Dragutin Zelenovic and is one of the first journals in Serbia publishing research on industrial systems, production management and group technology. Today, IJIEM is a part of international community and recognized as a journal that publish high quality international research on industrial engineering, manufacturing engineering and engineering management. All papers were reviewed by at least two international referees and were accepted after at least a revision. It is with great sadness that we report the death of Professor Dragutin Zelenovic. His contribution to the IJIEM and to the industrial, production management, and manufacturing engineering community is colossal. Hence, this issue is dedicated to Professor Dragutin Zelenovic.